Teachers and Parents Collaboration in Special Program Learning for Students with Special Needs - Ishartiwi, Ishartiwi; Azizah, Nur; Handoyo, Rendy Roos; Suseno, Adi (Angstrom Centre of Education, 2022)
Special school curriculum includes specialized program to help overcome obstacles according to students' condition. Not only limited to school, but the learning principles should also be applied through habituation and direct real-life practice. As a result, cooperation between teachers and parents are essential. However, its implementation still met with obstacles. This research survey aims at describing the problems in 80 special schools in Yogyakarta, with the respondent of 84 teachers for students with visual impairment, hearing loss, intellectual disability, physical disability, and autism. The data were collected via questionnaire, which include the aspect of cooperation practice, parents' roles, and parental involvement mechanism. In addition, the data were analyzed using descriptive approach, quantitative approach, and percentage technique. The result shows that most teachers for students with special needs are able to cooperate, involve parents, and share roles in cooperation mechanism. In conclusion, cooperation between teachers and parents is done to optimize students' success in special program learning by improving communication intensity and playing a role as facilitator.